Penerapan Sistem Tanggung Renteng dalam Kelancaran Pembayaran Kredit Nasabah Perspektif Ekonomi Islam: Studi Pada Permodalan Nasional Madani (PNM) Mekaar Cabang Aimas Sorong - Irlenia Febryanty Irawan; Suharmoko Suharmoko; Rokhimah Rokhimah (Prodi Ekonomi Syariah IAIN Sorong, 2022)
This study aims to determine the application of the joint responsibility system used in the launch of credit payments, to determine the costumer credit payment process and to determine the Islamic economic perspective regarding the joint responsibility system. The method used in this study is a qualitative apporoach, with the type of research used is Field Research. Methods of data collection is done by the process of observation, interviews and documentation. In testing the validity of the data the author uses two steps, namely observation and triangulation to obtain facts that actually occur. The results pf this study concluded that: the implementation of the joint responsibility system used was carrid out properly in accordance with the applicable rules and agreements, this was evidenced by the costumer group members applying the joint responsibility system if there were group members who did not pay instalments. The costumer credit payment process is carried out by means of the group members homes. The Islamic economic perspective regarding the financing of joint responsibility is in accordance with the concept of kafalah, namely the principle of kafalah bi al-mal which forms an agreement to work together and be responsible between fellow costumers of group members, to bear with each other using personal assets in the form of money between one member and member other if there is arrears by one of the members in terms of returning the financing credit.